Pertanggungjawaban Pidana terhadap Dokter yang Melakukan Malpraktck dalam Memberikan Pelayanan Kesehatan di Tengah Pandemi Covid 19 - Aditya Ryan Hidayat; I Nyoman Gede Sugiartha; I Made Minggu Widyantara (Warmadewa Press, 2021)
Malpractice is an act of wrongdoing and action; thus, medical malpractice is the act of a health worker who is wrong in carrying out the medical profession (Professional misconduct) both from the point of view of ethical norms or leg al norms. The formulation of the problems in this study are (I) What is the legal arrangement for doctors in providing health services in the midst of the Covid 19 pandemic What is the form of criminal responsibility for doctors who commit malpractice in providing health services in the midst of the Covid I 9 pandemic. This study uses the research method of normative Jaw. This study uses two problem approach methods, namely the statutory approach and the legal concept approach. This study also uses three sources of legal materials, namely primary, secondary and tertiary legal materials. The purpose of this study is to determine the legal arrangements that govern health services in the midst of the Covid-19 pandemic. The main source of this research is the Criminal Code, Law Number 36 Year 2009 and Law Number 29 Year 2004. The results obtained from this study are criminal sanctions that can be imposed on doctors regarding malpractice in the middle. The Covid 19 pandemic is article 267 paragraph (I), 294 paragraph (2), 359, 361 KUHP, and article 190 of Law Number 36 of 2009 concerning Health, as well as article 79 of Law Number 29 of 2004 concerning Medical Practice. For the government to pay more attention to the health sector, especially regarding malpractice